Into the storm: the imbalance in the yin-yang immune response as the commonality of cytokine storm syndromes - Armstrong, Amy; Tang, Yuting; Mukherjee, Neelam; Zhang, Nu; Huang, Gang (Frontiers in Immunology, 2024)
There is a continuous cycle of activation and contraction in the immune response against pathogens and other threats to human health in life. This intrinsic yin-yang of the immune response ensures that inflammatory processes can be appropriately controlled once that threat has been resolved, preventing unnecessary tissue and organ damage. Various factors may contribute to a state of perpetual immune activation, leading to a failure to undergo immune contraction and development of cytokine storm syndromes. A literature review was performed to consider how the trajectory of the immune response in certain individuals leads to cytokine storm, hyperinflammation, and multiorgan damage seen in cytokine storm syndromes. The goal of this review is to evaluate how underlying factors contribute to cytokine storm syndromes, as well as the symptomatology, pathology, and longterm implications of these conditions. Although the recognition of cytokine storm syndromes allows for universal treatment with steroids, this therapy shows limitations for symptom resolution and survival. By identifying cytokine storm syndromes as a continuum of disease, this will allow for a thorough evaluation of disease pathogenesis, consideration of targeted therapies, and eventual restoration of the balance in the yin-yang immune response.